Public Diplomacy as a Foreign Policy Tool. Theoretical Scope and the Peruvian Perspective - Paredes Moreno, Alejandro (2019)
Public diplomacy, as a central element in the design and execution of foreign policy strategies, has as its central element the new paradigm of communications and the multiplicity of actors that are empowered by it. In that sense, a theoretical study of this type of diplomacy; as well as a perspective work for the Peruvian case -whichseeks to lay the foundations for the design of a national strategy in this regard- is central to be able to promote our foreign policy in all areas, through the coherentuse of our potential and search for nichesto improve our capabilities in the international arena.